2013
DOI: 10.1038/ng.2742
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analysis identifies 13 new risk loci for schizophrenia

Abstract: Schizophrenia is a heritable disorder with substantial public health impact. We conducted a multi-stage genome-wide association study (GWAS) for schizophrenia beginning with a Swedish national sample (5,001 cases, 6,243 controls) followed by meta-analysis with prior schizophrenia GWAS (8,832 cases, 12,067 controls) and finally by replication of SNPs in 168 genomic regions in independent samples (7,413 cases, 19,762 controls, and 581 trios). In total, 22 regions met genome-wide significance (14 novel and one pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
1,308
4
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 1,440 publications
(1,359 citation statements)
references
References 94 publications
41
1,308
4
6
Order By: Relevance
“…The Schizophrenia Working Group of the Psychiatric Genomics Consortium study [2014] included analyses that sought to relate credible GWAS risk variants to genome‐wide eQTL data, finding rs11191419 to be in strong linkage disequilibrium (r 2  = 0.85) with an eQTL SNP (rs7096169) influencing AS3MT expression in blood. Using several brain eQTL datasets, Roussos et al [2014] identified SNPs influencing BORCS7 (C10ORF32) , AS3MT , WBP1L , and NT5C2 expression that are in linkage disequilibrium with rs7085104, identified in an earlier GWAS of schizophrenia [Ripke et al, 2013], which we found to be in strong linkage disequilibrium (r 2  = 0.79) with rs11191419 in the samples genotyped in the present study. These authors also assessed whether schizophrenia‐associated eQTLs were located in predicted cis ‐regulatory elements (CREs); expression of BORCS7 and AS3MT was reported to be influenced by SNPs within individual CRE, while expression of NT5C2 was associated with SNPs in 14 such elements [Roussos et al, 2014].…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…The Schizophrenia Working Group of the Psychiatric Genomics Consortium study [2014] included analyses that sought to relate credible GWAS risk variants to genome‐wide eQTL data, finding rs11191419 to be in strong linkage disequilibrium (r 2  = 0.85) with an eQTL SNP (rs7096169) influencing AS3MT expression in blood. Using several brain eQTL datasets, Roussos et al [2014] identified SNPs influencing BORCS7 (C10ORF32) , AS3MT , WBP1L , and NT5C2 expression that are in linkage disequilibrium with rs7085104, identified in an earlier GWAS of schizophrenia [Ripke et al, 2013], which we found to be in strong linkage disequilibrium (r 2  = 0.79) with rs11191419 in the samples genotyped in the present study. These authors also assessed whether schizophrenia‐associated eQTLs were located in predicted cis ‐regulatory elements (CREs); expression of BORCS7 and AS3MT was reported to be influenced by SNPs within individual CRE, while expression of NT5C2 was associated with SNPs in 14 such elements [Roussos et al, 2014].…”
Section: Discussionsupporting
confidence: 57%
“…Variants on chromosome 10q24.32‐q24.33 exhibit robust association with schizophrenia [Schizophrenia Psychiatric Genome‐Wide Association Study Consortium, 2011; Aberg et al, 2013; Ripke et al, 2013; Schizophrenia Working Group of the Psychiatric Genomics Consortium, 2014], but, like many regions implicated by GWAS, the actual susceptibility genes cannot be easily resolved through genetic data alone. Using a highly sensitive method for assessing variable cis ‐effects on gene expression [Yan et al, 2002; Bray et al, 2003a,2003b], we have found that several of the principal candidate genes at this locus exhibit altered cis ‐regulation in the developing and adult human brain in association with the most strongly supported schizophrenia risk variants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the results of genetic replication studies between SCZ and the DISC1 gene must be interpreted with extreme caution, 5 a critical issue in positive DISC1 association studies is a lack of replication for the same alleles in the same direction and the same haplotypes across the studies. In addition, recent genome-wide association studies (GWAS) 6,7 as well as a large association study 8 and a meta-analysis of variants in the DISC1 gene 9 failed to replicate significant associations of the DISC1 gene with SCZ. The second concern is a gender-specific association of DISC1 in SCZ.…”
mentioning
confidence: 99%